Developing Multi-Literacy Skills by Creating Graphic Story in Literature Class: A Project-Based Learning Approach - Rahmad Hidayat; Fajar Susanto (Universitas Jambi, Magister Program of English Education Department, 2020)
The research aims to develop multi-literacy skills by creating a literary graphic story as a creative and innovative way for English Department students in learning literature. By creating an adaptation from text to picture, students are expected to improve their ability to understand literary works and express their creative and innovative skills. This is a qualitative study implementing the Project-based Learning (PBL) approach in literature class, which aims to produce graphic stories as the output of studying literature. Students do not only understand the literary theories but also make something out of their understanding. The scaffolding instruction method was employed to examine practices of improving multiliteracy skills. A detailed action research plan, including preliminary observation in the classroom, action plan, intervention, and guiding, is applied. The investigation related to the barriers in doing the project is going to be conducted as well. Reader Response criticism is introduced to students in the reading and analyzing stage as a useful method to develop their critical thinking in evaluating the literary works they read. We argue that the students improve their reading skills, writing skills and producing graphic story stories based on their own interpretation of the literary text, which is proven by the summary and conversation texts they produce in the graphic stories. They also develop their creativity by producing images and pictures as the result of the literary adaptation process. There are two significant outcomes of the project: developing literary text understanding as well as producing the original graphic story.